Genetic analysis of the M RNA segment of Crimean-Congo hemorrhagic fever virus strains in Turkey - Ozdarendeli, A.; Aydin, K.; Tonbak, S.; Aktas, M.; Altay, K.; Koksal, I.; Kalkan, A. (Springer Wien, 2008)
Crimean-Congo hemorrhagic fever (CCHF) virus is member of the genus Nairovirus of the family Bunyaviridae. All members of the family Bunyaviridae are enveloped viruses containing tripartite, negative polarity, single-stranded RNA. CCHF is characterized by high case mortality, occurring in Asia, Africa, the Middle East and Europe. During recent years, outbreaks have been reported in Turkey. However, little information is available on the genetic diversity of CCHF virus in Turkey. In this study, a total of 1227 adult ticks were collected from domestic ruminants (796 specimens from cattle, 399 specimens from goats and 32 specimens from sheep). The presence of the M segment of CCHF virus was determined in 4 of 40 (10%) Hyalomma marginatum marginatum pools, in 2 of 38 (7.89%) Rhipicephalus bursa pools, and in 1 of 7 (7%) Boophylus annulatus pools. Hyalomma anatolicum anatolicum pools gave negative RT-PCR result against CCHF virus. Serum samples from seven patients infected with CCHF were selected and subjected to RT-PCR to amplify partial M segment of CCHF virus. This report introduces the first data on partial nucleotide sequences of M RNA segments of CCHF virus strains circulating in Turkey, isolated from ticks.
Keywords: Russia; Ticks; Diversity; Outbreak; Asia